Long-term stabilisation of grid connected wind farms with FACTS controllers. (16th March 2010) - Kumar, N. Senthil; Khan, M. Abdullah
The increasing power demand has led to the growth of new technologies that play an integral role in shaping the future energy market. Keeping in view of the environmental constraints, grid connected wind turbines are promising in increasing system reliability. This paper presents the impact of FACTS controllers on the long-term dynamic stability of power systems connected with wind farms based on doubly fed induction generator systems. The stability assessment is made first for a three-phase short circuit without the FACTS controllers in the power network and then with the FACTS controllers. The long-term dynamic simulation results yield information on: 1) the impact of faults and slow wind speed changes on the performance of wind driven induction generators; 2) the change in controllable parameters of the FACTS controllers following the faults and wind speed changes; 3) transient reactive power ratings of FACTS controllers for enhancement of rotor speed stability of induction generators and angle stability of synchronous generators.